Conversations with families of children with disabilities : insights for teacher understanding - Puig, Victoria; Recchia, Susan (New York, NY : Routledge, 2020)
"Conversations with Families of Children with Disabilities creates a space for diverse families of children with disabilities to share their stories with pre-service and in-service teachers. Specifically designed for professionals preparing to work with families of children with disabilities, this text invites the reader to listen in as families reflect on their personal journeys in conversation with the authors. This powerful book helps educators develop a deeper understanding of families and enhance their capacity for authentic partnerships"--
Introduction -- A mother and grandmother come together as caregivers -- A mother learns to advocate for a preschooler with complex needs -- A family reflects on the challenges and achievements in their daily lives -- A mother reclaims her strength and confidence negotiating the complexities of schooling for her child -- Parents collaborate to support their sons' health and educational achievement -- A family reflects on their achievements and dreams -- An unexpected reciprocity : guest speakers learn by sharing their stories -- Concluding thoughts.
OCLC-licensed vendor bibliographic record.
Keywords: Special education -- Parent participation; Special education -- Psychological aspects; Special education teachers -- Training of; Parent-teacher relationships; EDUCATION / General